Representações sociais de autonomia e autogestão de catadores de materiais recicláveis e apoiadores da Coopervida, São Carlos/SP - Oliveira, Letícia Dal Picolo Dal Secco de (2018)
The development of solidary-economic enterprises (SEE) in Brazil has contradictions, those highlighted in studies of Social Psychology of Work related to the transformations of meanings and identities of these organizations' subjects by internalization of solidary-economic values, even having organization and internal relationships influenced by capitalist hegemonic culture. The interaction with supporters is pointed out as a contribution for new values and principles working in organizations. These issues apply to cooperatives of recyclable waste pickers considering their precarious material and symbolic conditions of work and life that unfold into difficulties for signifying new proposed relationships. A potentiality of solidary economy (SE) refers to individual and collective gain of autonomy resulting in self-management processes, which is criticized in researches that characterize SEE as reproducing exploitation relationships for being perversely included in the competitiveness of economic market. It is understood that the study of social representations (SR) contributes to the investigation of these theoretical disputes by unveiling in practice the changes in identity and meaning came out from negotiations carried out in dialogical processes of interaction, elucidating conflicted issues in tension in the public sphere, as it is the case of SE potentialities. Thus, the aim has been to understand the SRs of pickers and supporters, in the same context, on autonomy and self-management. A case study has been carried out in the city of São Carlos-SP with direct observations, field diary records and individual semi-structured interviews. The central research field has been the Cooperative of Recyclable Waste Pickers of São Carlos (Coopervida), besides the institutions of supporters and public spaces of interaction. The analysis has been thematic and the informations have been triangulated. About pickers, autonomy is related to both an individual subject that does not fit in the cooperative and to the collective freedom of performing daily work. Self-management refers to the participation of cooperative members in the discussion spaces, respecting collective rules, that could enhance the work process and its results. Their SRs are anchored in their daily work. For the supporters, autonomy has multiple meanings (political, economic, social, collective and individual), and self-management is a dependent-on-autonomy process, corroborating with some theorists. Their SRs are anchored in the intersection between their life history and professional choices, reinforced by their participation in political articulation spaces. They consider that the participation of cooperative members in these spaces, as well as in educational processes, are primordial for the acquisition of knowledge necessary for a condition of autonomy. They permeate their SRs, environmental and social justice issues, with SE restricted to supporters of institutions based on it. The interactions established have led to some advances, albeit with several limitations, related to Coopervida's autonomy and self-management, however SE does not really form as part of it, but as a possibility. These elucidations are expected to contribute to both cooperative members and supporters understanding and reflecting on the limits and possibilities of their current conditions, as well as to trigger the articulation of joint strategies so that this interaction enables concrete transformations based on their aims.